2018
DOI: 10.1111/mec.14931
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of abdominal microbiomes in fungus‐growing ants

Abstract: The attine ants are a monophyletic lineage that switched to fungus farming ca. 55–60 MYA. They have become a model for the study of complex symbioses after additional fungal and bacterial symbionts were discovered, but their abdominal endosymbiotic bacteria remain largely unknown. Here, we present a comparative microbiome analysis of endosymbiotic bacteria spanning the entire phylogenetic tree. We show that, across 17 representative sympatric species from eight genera sampled in Panama, abdominal microbiomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 102 publications
(203 reference statements)
3
44
0
Order By: Relevance
“…Host transmission of heritable extracellular symbionts has been hypothesized to result in long-term associations between some social insects and specialized microbiota. Termites, social corbiculate bees, and clades of ants consistently host microbial phylotypes over evolutionary timescales, as indicated by patterns of phylogenetic congruence of microbial communities with hosts (Russell et al, 2009;Dietrich et al, 2014;Sanders et al, 2014;Kwong et al, 2017;Lukasik et al, 2017;Bourguignon et al, 2018;Sapountzis et al, 2019). Although this indicates vertical transmission across generations, most symbioses are characterized by the presence of at least some degree of host switching, suggesting that horizontal transmission persists across host clades (Koch et al, 2013;Sanders et al, 2014;Kwong et al, 2017;Bourguignon et al, 2018).…”
Section: Sociality Supports Persistent Symbiotic Gut Microbiotamentioning
confidence: 99%
“…Host transmission of heritable extracellular symbionts has been hypothesized to result in long-term associations between some social insects and specialized microbiota. Termites, social corbiculate bees, and clades of ants consistently host microbial phylotypes over evolutionary timescales, as indicated by patterns of phylogenetic congruence of microbial communities with hosts (Russell et al, 2009;Dietrich et al, 2014;Sanders et al, 2014;Kwong et al, 2017;Lukasik et al, 2017;Bourguignon et al, 2018;Sapountzis et al, 2019). Although this indicates vertical transmission across generations, most symbioses are characterized by the presence of at least some degree of host switching, suggesting that horizontal transmission persists across host clades (Koch et al, 2013;Sanders et al, 2014;Kwong et al, 2017;Bourguignon et al, 2018).…”
Section: Sociality Supports Persistent Symbiotic Gut Microbiotamentioning
confidence: 99%
“…[79] Since in addition to the mutualistic fungus they cultivate for food, fungus-growing ants harbor complex microbiomes, [80,81] they represent a good model for understanding a multilayered symbiosis. For example, fungus-growing ants of the genus Atta, form a symbiosis with fungi that they cultivate as the main food source for the colony.…”
Section: Mining the Species Diversity For Insights Into Symbiotic Assmentioning
confidence: 99%
“…For example, fungus-growing ants of the genus Atta, form a symbiosis with fungi that they cultivate as the main food source for the colony. [79] Since in addition to the mutualistic fungus they cultivate for food, fungus-growing ants harbor complex microbiomes, [80,81] they represent a good model for understanding a multilayered symbiosis. Also, studies in the African turquoise killifish Nothobranchius furzeri, one of the shortest lived vertebrate species, revealed that the gut microbiota plays a key role in modulating life span [82] (see also Finlay et al [83] in this issue).…”
Section: Mining the Species Diversity For Insights Into Symbiotic Assmentioning
confidence: 99%
“…Nevertheless, the correspondence between gut bacteria and historical biogeography suggests that strong constraints on the assembly of attine gut bacterial communities are also at play. As Sapountzis et al () note, future studies of higher‐attine lineages that independently recolonized South America will clarify the extent of the geographic and phylogenetic nature of these constraints. Moreover, although the higher attines that diversified in Middle America have higher gut bacterial densities than do other attines, even these species appear to have fewer gut bacteria than other, non‐attine ants whose gut bacteria confer known nutritional benefits (Rubin, Kautz, Wray, & Moreau, ; Sanders et al ).…”
mentioning
confidence: 96%
“…Sapountzis, Nash, Schiøtt, and Boomsma () go inside the ants themselves to examine gut bacterial communities across 17 attine species, representing the major transitions in fungal agriculture. Comparing attines across dietary transitions, they find some evidence for increased bacterial densities and reduced bacterial diversity in ant guts and associated abdominal material with increased dietary specialization, consistent with a concomitant shift towards a more specialized gut bacterial community (Figure ).…”
mentioning
confidence: 99%